Psychometric Properties of the Personality Inventory for DSM-5 (PID-5) in Brazilian Samples - Oliveira,Sérgio Eduardo Silva de (2021)
Abstract This study aimed to investigate the psychometric properties of the Personality Inventory for DSM-5 (PID-5) in Brazilian community and clinical samples. This research included 1,210 people, 554 of them with psychopathology indicators. The participants answered the PID-5 and the Self-Reporting Questionnaire, in addition to a sociodemographic and health data questionnaire that included the six items of the suicidality module of the Mini International Neuropsychiatric Interview. The results showed that the 25 facets of the PID-5 had adequate reliability coefficients and evidence of unidimensionality. The instrument’s five-factor structure was replicated with high levels of congruence with the representative sample from North America. PID-5 scores were statistically different between clinical and community groups and were positively correlated with measures of suicide risk and psychopathological symptoms. This study presents the psychometric properties of PID-5 and its suitability for use in the Brazilian population.